Sources Of Financing For Exports Of Agricultural Products - Tajenova Gulbahar Esbosinovna; Seyfullaeva Ayzada (Periodica Journal, 2024)
The article mainly mentions the sources of financing for the export of agricultural products and the importance of loans from commercial banks in financing the export of agricultural products.
Keywords: Export Of Products; Financing; Commercial Banks; Credit